Grapefruit Juice Facilitates Cortisol Replacement Therapy: Role of CYP3A Variant Alleles - Drent, Marjolein; Wijnen, Petal; Bekers, Otto; Bast, Aalt (Archives of Clinical and Medical Case Reports, 2021)
Glucocorticosteroid (GC) replacement therapy is required in several clinical situations. However, tapering down the GC doses may lead to a steroid withdrawal syndrome. We describe the case of a patient presenting with Cushing’s syndrome due to a pituitary adrenocorticotropic hormone (ACTH) producing adenoma. After successful surgery, cortisol replacement was started. Unfortunately, tapering the hydrocortisone (HC) dose failed. We hypothesized that the presence of cytochrome P450 (CYP)3A variant alleles might at least partly explain the inappropriate response to HC. The patient appeared to be a CYP3A5 intermediate metabolizer (*1/*3) and a slightly more rapid CYP3A4 metabolizer (*1A/*1B), both accounting for an increased HC metabolism. Cortisol is metabolized via various biotransformation pathways which could be affected by grapefruit juice. After the patient started to take the HC with grapefruit juice, she felt better, and it became easier to taper down the daily HC dose. The peak cortisol dose was the same with and without the use of grapefruit juice, whereas the cortisol level six hours after the morning dose of HC was 20% higher than in the situation without grapefruit juice. In conclusion, grapefruit juice enhances cortisol availability by increasing 11β-hydroxysteroid dehydrogenase (HSD) type 1 activity and simultaneously inhibiting cortisol metabolism by inhibiting the CYP3A enzymes. The presence of CYP polymorphisms appeared to be a substantial susceptibility risk factor in the cortisol metabolism and the development of a GC withdrawal syndrome.